Pengaruh Status Sosial Ekonomi dan Manajemen Keuangan Pribadi Terhadap Perilaku Konsumtif Mahasiswa Universitas KH. A. Wahab Hasbullah - Purwatiningsih Purwatiningsih; Nia Aprilia Bisari (Journal of Applied Accounting, 2026)
This study aims to analyze the influence of socio-economic status and personal financial management on the consumptive behavior of students at KH. A. Wahab Hasbullah University. The research method used is quantitative with a causal-associative design. Sampling was conducted using probability sampling, targeting 100 active students who were categorized as frequently engaging in consumptive behavior. Data were collected via online questionnaires and analyzed using multiple linear regression. The results show that socio-economic status has a significant effect on consumptive behavior, whereas personal financial management has a significant effect on students' consumptive behavior, both partially and simultaneously. The coefficient of determination value of 0,773 indicates that one of the independent variables explains 77,3% of the variation in students' consumptive behavior, while the remainder is influenced by other factors. The implication of this study is that targeted financial education is highly necessary so that students are able to plan, manage, and control the use of personal finances wisely. Keywords: socioeconomic status, personal financial management, consumptive behavior, university students.